3D printing of silicone meniscus implant via extrusion technique - Liu, Hang (2018)
The human knee meniscus provides physical protection through transmitting loads, providing shock absorption, and distributing high peak stresses on the underlying surfaces. However, current surgical and repair methods for complex meniscus injuries and large osteochondral lesions often do not give satisfactory longterm results. In this research, silicone meniscus implant is proposed as a possible solution for the meniscus treatment. The extrusion-based additive manufacturing (AM) of heat-cured silicone elastomer is presented to fabricate the silicone meniscus implant. Due to the soft nature of heat-cured silicone, AM is technically challenging. This research aims to find out the optimized combination of process parameters through a series of process studies, in which several shapes, such as T bone, cylinder, were fabricated to find out the optimal printing conditions. At last, several silicone meniscus implants were printed, which are close to required dimensions. In the future, the experimental setup can be improved, and several tests, such as the compression test and tensile test, should be done for the 3D meniscus implant samples and biological test should be done before it applied into medical areas.